Microbiome Characterization of Infected Diabetic Foot Ulcers in Association With Clinical Outcomes: Traditional Cultures Versus Molecular Sequencing Methods - Mudrik-Zohar, Hadar; Carasso, Shaqed; Gefen, Tal; Zalmanovich, Anat; Katzir, Michal; Cohen, Yael; Paitan, Yossi; Geva-Zatorsky, Naama; Chowers, Michal (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Infected diabetic foot ulcers (IDFU) are a major complication of diabetes mellitus. These potentially limb-threatening ulcers are challenging to treat due to impaired wound healing characterizing diabetic patients and the complex microbial environment of these ulcers. Aim: To analyze the microbiome of IDFU in association with clinical outcomes. Methods: Wound biopsies from IDFU were obtained from hospitalized patients and were analyzed using traditional microbiology cultures, 16S rRNA sequencing and metagenomic sequencing. Patients' characteristics, culture-based results and sequencing data were analyzed in association with clinical outcomes. Results: A total of 31 patients were enrolled. Gram-negative bacteria dominated the IDFU samples (79%, 59% and 54% of metagenomics, 16S rRNA and cultures results, respectively, p<0.001). 16S rRNA and metagenomic sequencing detected significantly more anaerobic bacteria, as compared to conventional cultures (59% and 76%, respectively vs. 26% in cultures, p=0.001). Culture-based results showed that Staphylococcus aureus was more prevalent among patients who were treated conservatively (p=0.048). In metagenomic analysis, the Bacteroides genus was more prevalent among patients who underwent amputation (p<0.001). Analysis of metagenomic-based functional data showed that antibiotic resistance genes and genes related to biofilm production and to bacterial virulent factors were more prevalent in IDFU that resulted in amputation (p<0.001). Conclusion: Sequencing tools uncover the complex biodiversity of IDFU and emphasize the high prevalence of anaerobes and Gram-negative bacteria in these ulcers. Furthermore, sequencing results highlight possible associations among certain genera, species, and bacterial functional genes to clinical outcomes.